Pengaruh Hidroterapi Terhadap Peningkatan Saturasi Oksigen Pada Pasien Gagal Jantung - Huwaina Af’idah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hydrotherapy also called hydrothermal therapy, is the use of water,in any of its forms, for the maintanance of health or the treatment of disease (Wardle, 2013). Footbath is a kind of hydrotherapy. There are many benefits of footbath hydrotherapy for patients with heart failure such as to improve and/or maintain functional ability and quality of life. The aim of this research is to identification the effectiveness of hydrotherapy for oxigen saturation of patients with heart failure. The methodology of this research is use quantitative design with one group pretest and posttest with intervention group design. This research did Maret 2023 in The Integrated Heart Centre Haji Adam Malik Medan Hospital. 16 Responden of this group. According demografi charachteristic results in intervention group found that according of age patients majority (62.5%) are older age with 56-65 years mean 55.06+ 8.71. Second half three respondent (62,5%) is men. According to education level majority respondent is Senior High School (62.5%). More than hal of respondent (62.5%) is Heart Failure Chronic > 60 months (5 years) (Mean + SD= 31,44 + 26,63). Almost all respondents (87,5%) had a family with history heart failure too. Pre and Post Paired t-test results are significant different for oxygen saturation at intervention groups (p<0,05) (SpO2: t= -1.581, p= 0.004 ). It means the effectiveness of hydrotherapy significantly can increase spO2. This research has found that significant different of oxigen saturation of patients with heart failure after hydrotherapy in intervention group.